Recognition and Enforcement of Annulled Foreign Arbitral Awards in the Country of Origin under the 1958 New York Convention: the US and French Approaches - Ay , Yunus Emre (Teisė, 2021)
The recognition and enforcement of annulled foreign arbitral awards in the country of origin under the 1958 New York Convention is subject to doctrinal discussions. A relevant article of the1958 New York Convention become the subject matter of many cases in some large economies. These cases and doctrinal views are very important for other countries that did not host such a case before their national courts. Therefore, the purpose of this paper is to analyse the relevant article of the 1958 New York Convention and compare delocalization and territorial theories.
Keywords: Foreign Arbitral Awards; Annulled Arbitral Awards; New York Convention; International Arbitration